A Study On The Effectiveness Of Ground Improvement Techniques / M.F Ahmad, N.A. Zakaria, M.R. Selamat - M.F, Ahmad; Zakaria, N.A.; Selamat, M.R. (Universiti Teknologi MARA Cawangan Pulau Pinang, 2003)
A railway track has been constructed connecting industrial petrochemical complexes in Terengganu to Kuantan Port, all are in the east coast of Peninsular Malaysia. The route passes mostly through low lying swampy areas which are seasonally affected by monsoon flooding. Site investigations conducted along the route had indicated the dominant presence of soft, fine grained and soft, loose, coarse grained soils, except in a few hill locations. As railway tracks are sensitive to settlement and have small tolerance for it, a massive ground improvement work was implemented at site. Because of high cost investment for equipment in the implementation of the ground improvement work, specialist contractors implementing them are local branches of international contractors. The non-availability of published local research on ground improvement techniques results in ineffective selection of technique for ground improvement work. With these limitations, based on experience from the field work on the railway track, work is on going to compare the effectiveness of ground improvement technique. The four main ground improvement methods that were implemented and will be studied are Prefabricated Vertical Drain (PVD), Vibro-Compaction (VC), Dynamic Compaction (DC), and Stone Column (VR). From actual field data collected, comparison between one form of improvement to another in terms of the original soil type corresponding to, amount of work required by, and constraints faced while carrying out each type of improvement will be studied.